PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN LIVE WORKSHEET TERHADAP MOTIVASI DAN HASIL BELAJAR IPA PESERTA DIDIK KELAS 4 SEKOLAH DASAR - Herman Yoseph Sarjimin; Sugeng Sutiarso; Suratinah (Jurnal Pendidikan Dasar, 2022)
The learning process at SD Negeri 1 Wana is included in the low criteria where the motivation and learning outcomes of students are still below the KKM. Science lessons are lessons that are indispensable in students' lives so that in learning it requires seriousness and a good sense of enthusiasm. The success of science learning in grade 4 of Wana Elementary School needs to be marked by good learning outcomes. Thus, it is necessary to make efforts to increase students' motivation and learning outcomes by using appropriate learning models and tools. quantitative approach and includes Quasi Experiment research as well as in this study using test questions and questionnaires. Based on the results of the study, there was an effect of the PBL learning model assisted by the LKPD live worksheet on motivation in the very good category. Based on the research results, the PBL learning model assisted by the LKPD Live Worksheet is feasible to use to improve student learning outcomes.